2018
DOI: 10.1016/j.joco.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Visual impairment and blindness in a population-based study of Mashhad, Iran

Abstract: PurposeTo determine the prevalence of visual impairment and blindness and related factors in the 1- to 90-year-old urban population of Mashhad.MethodsIn this cross-sectional study of 1- to 90-year-old residents of Mashhad, in northeastern Iran, sampling was done through random stratified cluster sampling (120 clusters). After selecting the samples and their participation in the study, all subjects had vision testing including measurement of visual acuity and refraction, as well as examinations with the slit-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
1
13
3
3
Order By: Relevance
“…Besides, the variation in a socioeconomic characteristic of the study population could also contribute to this difference. On the other hand, the result of this study is higher than studies done in the Gurage Zone of Ethiopia (12.1%) [15] and a national survey of Ethiopia (3.7%) [4], Afghanistan (13.9%) [9], Sri Lankan (19.6%) [10], Indian states (9.2-22.1%) [8,11,12], Malaysia (7%) [7], and Iran (3.09%) [6]. is difference might be due to the variation in sampling design and sample size in which those studies were done at the community level with a larger sample size.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Besides, the variation in a socioeconomic characteristic of the study population could also contribute to this difference. On the other hand, the result of this study is higher than studies done in the Gurage Zone of Ethiopia (12.1%) [15] and a national survey of Ethiopia (3.7%) [4], Afghanistan (13.9%) [9], Sri Lankan (19.6%) [10], Indian states (9.2-22.1%) [8,11,12], Malaysia (7%) [7], and Iran (3.09%) [6]. is difference might be due to the variation in sampling design and sample size in which those studies were done at the community level with a larger sample size.…”
Section: Discussioncontrasting
confidence: 76%
“…e possible reasons for this variation could be that females have had longer life expectancy than males, which in turn leads to developing eye conditions that could be increasing low vision [23]. Also, this might be happening because females could have unequal access for eye care services in some rural areas and the social stigma of wearing spectacles [18], whereas studies were done in Afghanistan, Sri Lankan, North India, and Iran reported that gender was not associated with low vision [6,[9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Table 4, which presents the prevalence of VI in similar studies, the prevalence of VI in our study was higher than some (de Winter et al, 2004; Friedman et al, 2004; Horowitz, 1994; Mitchell et al, 1997; Owsley et al, 2007a; Tielsch et al, 1995; West et al, 2003; Whitmore, 1989) and lower than some other studies (VanNewkirk et al, 2000; Waked, Saad, Mehanna, Sleilaty, & Kortbaoui, 2007), which could be due to differences in the definition or ethnicity and race of the participants. On the other hand, the prevalence of VI in our participants was 4–20 times higher when compared to its prevalence in similar age groups of community-dwelling people, as domestic studies have reported a prevalence of 2–11% (Hashemi, Khabazkhoob, Emamian et al, 2012; Hashemi, Khabazkhoob, Saatchi, Ostadimoghaddam, Yekta, 2017; Hashemi, Yekta, et al, 2017; Yekta et al, 2011; Yekta, Hashemi, Ostadimoghaddam, Shafaee, Norouzirad, Radaye-moghaddam, et al, 2013), which is far lower than our results. In line with our study, some other studies have also reported a higher prevalence of VI in NHRs as compared to community-dwelling older persons (de Winter et al, 2004; Horowitz, 1994; Klein et al, 1991; Mitchell et al, 1997; Owsley et al, 2007a; Taiel-Sartral et al, 1999; Tielsch et al, 1995; Van der Pols et al, 2000; VanNewkirk et al, 2000; West et al, 2003; Whitmore, 1989).…”
Section: Discussioncontrasting
confidence: 91%
“…It has been reported that approximately 4% of the world's population are visually impaired (Hashemi et al, 2017). This figure could significantly reduce if more efficient ocular dosage forms existed.…”
Section: Introductionmentioning
confidence: 99%